High temperature resistant reflective layer for wavelength conversion devices

JP7638218B2Active Publication Date: 2025-03-03MATERION PRECISION OPTICS SHANGHAI LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021552730
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-04-19
Publication Date
2025-03-03
Estimated Expiration
2039-04-19

Smart Images

  • Figure 0007638218000017
    Figure 0007638218000017
  • Figure 0007638218000018
    Figure 0007638218000018
  • Figure 0007638218000019
    Figure 0007638218000019
Patent Text Reader

Abstract

The wavelength converter (100) comprises a substrate (110), a reflective layer (120) on the substrate (110), and a wavelength conversion layer (130) on the reflective layer (120). The reflective layer (120) contains a binder (121) and reflective titanium dioxide nanoparticles (122). The nanoparticles (122) have a particle size of about 200 nanometers to about 500 nanometers. The reflective layer (120) has high thermal stability. A method for manufacturing the wavelength converter is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to wavelength conversion devices, such as phosphor wheels, that have a reflective layer that is resistant to high temperatures, and therefore are particularly suitable for use in projection display systems and visible light conversion devices that use solid-state lasers as light sources. [Background technology]

[0002] A phosphor wheel can be used to generate light with different wavelengths from a single light source. The wheel consists of a circular substrate with surface segments of different colors. When light (from a light source) is incident on the wheel and the wheel is rotated, the surface segments convert the light to different wavelengths.

[0003] For reflective phosphor wheels, the substrate reflects light, so it is desirable to maximize the reflectivity of the substrate. Aluminum (Al) coated substrates typically have an average reflectivity of 94% for wavelengths from about 420 nm to about 680 nm, while silver (Ag) coated substrates have an average reflectivity of 98%.

[0004] However, stability and durability are also concerns for reflective wavelength converters. After hundreds of hours of operation at high temperatures (higher than 150 °C), burnout at the laser incidence area is observed on Ag-coated substrates. Migration of silver ions in the coating layer at high temperatures may be responsible for this effect. This can lead to a decrease in optical performance of about 9%. Summary of the Invention [Problem to be solved by the invention]

[0005] Organosilicones with high reflectivity (>95%) have been used to form the reflective layer of wavelength conversion devices. However, they have poor thermal stability. At temperatures above 200°C, silicones degrade, usually starting to yellow and slowly burn. At temperatures above 195°C, the phosphor layer on the reflective layer also cracks after about 1000 hours. This undesirably shortens the service life of the phosphor wheel, and it has been observed that the light conversion efficiency drops sharply (>10% @200°C) due to thermal quenching. For high brightness (e.g., 300W laser power) applications, the operating temperature of the phosphor wheel is generally expected to exceed 200°C, making the use of silicones undesirable.

[0006] A substrate that has high reflectivity throughout its lifetime is desirable. It is also desirable to improve the reflectivity of the substrate while maintaining and improving reliable lifetime performance at low cost. Such substrates and reflective coatings / layers can be advantageously used in a variety of applications, such as light tunnels, projection display systems, and visible light conversion devices such as phosphor wheels used in such systems. [Means for solving the problem]

[0007] The present disclosure relates to compositions used to form reflective layers in wavelength conversion devices such as phosphor wheels or color wheels; reflective layers containing specific materials; and wavelength conversion devices with such reflective layers. Such reflective layers are resistant to temperature degradation at high operating temperatures (e.g., greater than 200°C to 250°C). Methods for making and using such compositions, layers, and devices are also disclosed herein.

[0008] Various embodiments herein disclose a wavelength conversion device comprising a substrate, a reflective layer on the substrate, and a wavelength conversion layer on the reflective layer, the reflective layer including (A) a binder and (B) reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers.

[0009] In some embodiments, the reflective nanoparticles are pure titanium dioxide (TiO2), aluminum oxide (Al2O3), or magnesium oxide (MgO). In other embodiments, the reflective nanoparticles are titanium dioxide (TiO2) surface modified with organic alcohols, siloxanes, aluminum oxide (Al2O3), zirconium dioxide (ZrO2), or silicon dioxide (SiO2).

[0010] The reflective layer may have a thickness of about 0.05 mm to about 0.15 mm. The mass ratio of the (B) reflective nanoparticles to the (A) binder may be about 1:2.5 to about 1:0.8.

[0011] The binder can be an organic binder or an inorganic binder. An example of an organic binder is a silicone such as octamethyltrisiloxane. An example of an inorganic binder is sodium silicate.

[0012] The reflective layer desirably has a reflectance of at least 95% for light having a wavelength of about 420 nm to about 680 nm. The phosphor layer may include phosphor particles dispersed in a glass, crystal, or ceramic material. The substrate may have a disk shape. The wavelength conversion may further include a motor for rotating the substrate. The substrate may be a metal, a non-metallic material, or a composite material.

[0013] Also disclosed are optical projection systems comprising the wavelength converting devices described herein.

[0014] Also disclosed in various embodiments is a method for manufacturing a wavelength conversion device, comprising the steps of applying to a substrate a composition comprising (A) a binder and (B) reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers to form a reflective layer on the substrate, and forming a wavelength conversion layer on the reflective layer.

[0015] The composition, as applied to the substrate, can have a viscosity of about 0 centipoise (cP) to about 1500 cP. The method can further include curing the composition at a temperature of about 85° C. to about 150° C. The composition can be applied by dispensing, spraying, brushing, flowing, coating, or silk-screen printing.

[0016] These and other non-limiting features of the present disclosure are disclosed in greater detail below. [Brief description of the drawings]

[0017] The following is a brief description of the drawings, which are presented for purposes of illustrating exemplary embodiments disclosed herein and are not presented for purposes of limiting the same.

[0018] [Figure 1A] 1 is a schematic diagram of an exemplary visible light conversion device according to the present disclosure, including a substrate, a highly reflective layer, and a phosphor layer.

[0019] [Figure 1B] FIG. 1B is a side cross-sectional view of the exemplary visible light conversion device of FIG. 1A.

[0020] [Figure 1C] FIG. 2 is an exploded view of the layers of the visible light conversion device.

[0021] [Figure 2A] 4 is a graph showing the relationship between reflectance and reflective layer thickness for a first phosphor wheel of the present disclosure.

[0022] [Figure 2B] 11 is a graph showing the relationship between reflectance and reflective layer thickness for a second phosphor wheel of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] A more complete understanding of the components, processes, and devices disclosed herein can be obtained by reference to the accompanying drawings, which are merely schematic representations based on convenience and ease of illustrating the disclosure, and are therefore not intended to illustrate relative sizes and dimensions of the devices or their parts, and / or to define or limit the scope of the example embodiments.

[0024] Although specific terms are used in the following description for the sake of clarity, these terms are intended to refer only to the particular structures of the embodiments selected for illustration in the drawings, and are not intended to define or limit the scope of the present disclosure. In the drawings and the following description, it should be understood that like numeral designations refer to components of similar function.

[0025] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0026] As used in this specification and claims, the terms "comprise(s)", "include(s)", "having", "has", "can", "contain(s)", and variations thereof, as used herein, are intended to be open-ended transitional phrases, terms, or words that require the presence of the specified ingredients / steps and allow for the presence of other ingredients / steps. However, such statements should also be construed as describing the composition or process as "consisting of" and "consisting essentially of" the recited ingredients / steps, thereby allowing for the presence of only the specified ingredients / steps, including unavoidable impurities that may result therefrom, and excluding other ingredients / steps.

[0027] Numerical values ​​in the specification and claims of this application should be understood to include and determine the same values ​​when reduced to the same number of significant figures, and numerical values ​​that differ from the stated value by no more than the experimental error of conventional measuring techniques.

[0028] All ranges disclosed herein are inclusive of the recited endpoints and are independently combinable (e.g., the range "2 grams to 10 grams" includes the endpoints, 2 grams and 10 grams, and all intermediate values).

[0029] The terms "about" and "approximately" can be used to include any numerical value that can vary without changing the basic function of its value. When used in conjunction with a range, "about" and "approximately" also disclose the range defined by the absolute values ​​of the two endpoints, for example, "about 2 to about 4" also discloses the range "2 to 4". In general, the terms "about" and "approximately" can refer to plus or minus 10% of the indicated number.

[0030] As used herein, the terms "excitation light" and "excitation wavelength" refer to input light that is subsequently converted, e.g., light produced by a laser-based illumination source or other light source. The terms "emission light" and "emission wavelength" refer to the converted light, e.g., the resultant light produced by a phosphor exposed to excitation light.

[0031] The term "inorganic" as used herein means that the "inorganic" does not contain carbon. For the avoidance of doubt, the terms "inorganic binder", "inorganic adhesive", "inorganic coating", and "inorganic adhesive" in this disclosure do not contain carbon.

[0032] For reference, red typically refers to light having a wavelength of about 780 nanometers to about 622 nanometers. Green typically refers to light having a wavelength of about 577 nanometers to about 492 nanometers. Blue typically refers to light having a wavelength of about 492 nanometers to about 455 nanometers. Yellow typically refers to light having a wavelength of about 597 nanometers to about 577 nanometers. However, this may depend on the context. For example, these colors may be used to label various parts and distinguish them from one another.

[0033] The present disclosure relates to wavelength conversion devices that include a reflective layer having a specific composition. In particular, the reflective layer comprises (A) a binder, which may be organic or inorganic, and (B) reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers, including about 350 nanometers to about 450 nanometers. These reflective layers operate at high temperatures (e.g., above 200° C. or 250° C.) while maintaining other optical and mechanical parameters, such as total reflectance.

[0034] Whether the reflective layer maintains high stability can be determined by one of two methods. In the first method, the phosphor wheel with the reflective layer is placed in an oven and aged at 250°C. The reflectance is tested every 100 hours for a minimum of 500 hours, and the reflective layer is observed for cracks. If the reflectance changes less than 2% between the 300, 400, and 500 hour measurements, and the reflective layer is free of cracks, the reflective layer is considered to maintain high stability. In the first method, the phosphor wheel with the reflective layer is placed in an oven and aged at 250°C. The conversion efficiency of the phosphor wheel is tested every 100 hours for a minimum of 500 hours, and the reflective layer is observed for cracks. If the conversion efficiency changes less than 2% between the 300, 400, and 500 hour measurements, and the reflective layer is free of cracks, the reflective layer is considered to maintain high stability. Only one of these two methods needs to be passed for the reflective layer to be considered to maintain high stability.

[0035] 1A and 1B, a wavelength conversion device of the present disclosure is depicted. The wavelength conversion device is shown in the form of a phosphor wheel 100. FIG. 1A is a schematic diagram of the phosphor wheel 100, and FIG. 1B is a side cross-sectional view of the phosphor wheel 100. The phosphor wheel 100 includes a substrate 110 having a reflective layer 120 formed thereon, and a phosphor layer 130 applied on the reflective layer 120. The reflective layer is formed from a composition as further described herein. As shown here, the reflective layer 120 is formed from an inorganic binder or organosilicone (A), indicated by reference numeral 121, and reflective nanoparticles, indicated by reference numeral 122.

[0036] The substrate 110 is typically a metal with high thermal conductivity, for example aluminum or an aluminum alloy, copper or a copper alloy, silver or a silver alloy, or other metal with high thermal conductivity. The substrate may be made of non-metallic materials or composite materials, for example glass, sapphire or diamond. The substrate is typically in the shape of a disk or ring. The smoothness or roughness of the substrate surface is not important. However, it is desirable that the surface of the substrate on which the reflective layer 120 is formed is clean and free of dirt, oil, organic or biological residues thereon. In the case of surfaces with low surface energy, adhesion can be improved by priming or by special surface treatments such as chemical or plasma etching or ozone cleaning.

[0037] The phosphor layer 130 contains at least one phosphor. Examples of suitable phosphors include yttrium aluminum garnet (YAG), silicates, and nitrides. The phosphors can have a particle size of about 10 to about 30 microns. The phosphor layer is usually in the form of annular phosphor segments and contains various types of phosphors to convert the excitation light to green, yellow, or red. Typically, a blue light laser (having a wavelength of about 440 nm to about 460 nm) is used to excite the phosphor segments on the phosphor wheel. The phosphor wheel can also have one or more gaps to allow blue source light to pass unconverted.

[0038] The phosphor wheel 100 of Figures 1A and 1B can be used by mounting the substrate on a motor for high speed rotation. Typically, the substrate is rotated during use, but the device can also be used in a static (non-rotating) configuration, in which case it may not be referred to as a phosphor wheel. The rotation of the phosphor wheel is indicated in Figure 1A by the arrow passing through the substrate 110 and rotating about an axis AA perpendicular to the plane of the substrate 110. As a result, light of different wavelengths is generated sequentially.

[0039] As seen in FIG. 1A and FIG. 1B, excitation light 123 (i.e., exciting or input light) at an excitation wavelength from a light source (not shown) (e.g., a laser-based illumination source) is focused onto the phosphor layer. Emission light 124 (i.e., emitted or converted light) at an emission wavelength is generated by the phosphor layer. In this way, the phosphor layer converts the light spectrum from the excitation light in a first range of spectral wavelengths into emitted (or re-emitted) light in a second, different range of spectral wavelengths. When the light 123 at the excitation wavelength (e.g., laser beam blue light) is focused onto the phosphor layer, light 124 at an emission wavelength (e.g., yellow light) is emitted in all directions, including toward the substrate. A reflective layer 120 is used to reflect and redirect this emission light away from the substrate so that it is emitted on the same side of the substrate as the excitation light is received. The emission light can be collected (e.g., by a lens) and used in subsequent downstream processes.

[0040] The reflective layer 120 comprises (A) a binder, which may be organic or inorganic, and (B) reflective nanoparticles having a particle size of about 200 nanometers to about 500 nanometers. In a more specific embodiment, the reflective nanoparticles have a particle size of about 350 nanometers to about 450 nanometers.

[0041] For the binder (A), a suitable material should operate for extended periods (at least 20,000 hours) over a temperature range of -45°C to 250°C (-49°F to +482°F). Desirably, the binder can operate for such extended periods at temperatures in excess of 200°C. The binder (A) can be an organic binder or an inorganic binder.

[0042] An example of an organic binder is an organosilicon such as octamethyltrisiloxane, a reflective resin. Such silicones are commercially available from Dow or Sumitomo Chemical. The organosilicon can be mixed with an organic solvent before coating, which can include methylsiloxane. An example of an organic solvent is sold by Dow Corning Corporation under the name OS-20. This is a volatile solvent and is used as a diluent to adjust the solution viscosity. The mixed silicone / solvent is homogenized according to process requirements, and a silicone oil thinner can be added to adjust the viscosity before the mixture is put into a mixer for mixing.

[0043] Alternatively, the binder (A) may be an inorganic binder having specific properties. Desirably, the inorganic binder has a coefficient of thermal expansion (CTE) of about 0.5 to about 25 ppm / °C. In a specific embodiment, the inorganic binder is sodium silicate. Sodium silicate has the formula (Na2SiO3) n is the common name for a compound of the formula (I), which may alternatively be considered a polymer, as shown below in formula (I). [ka]

[0044] Sodium silicate has both anhydrous and hydrated forms Na2SiO3·nH2O, where n=5, 6, 8, or 9. Sodium silicate can be characterized by the mass ratio of silicon dioxide (SiO2) to sodium oxide (Na2O). The mass ratio of SiO2:Na2O can vary from 2:1 to 3.75:1. In certain embodiments, the mass ratio of SiO2:Na2O is about 2.5:1 to about 3.75:1, or about 2:1 to about 3:1. Sodium silicate is typically provided as an aqueous solution.

[0045] In other embodiments, the inorganic binder may be made of other inorganic materials than sodium silicate. These inorganic materials may be silicates, aluminates, phosphates, borates or inorganic sol-gels. Examples of inorganic sol-gels include sol-gels made of silicon dioxide (SiO2) or aluminum oxide (Al2O3).

[0046] In another exemplary embodiment, the inorganic binder is formed from a first and a second component. The total dissolved solids (TDS) properties of the inorganic binders used are shown in the table below. [Table 1]

[0047] This particular inorganic binder is prepared by mixing the first component and the second component and stirring for about 2 to about 3 hours at a temperature of about 25 to about 30° C. The ratio of the first component to the second component is about 1:1 to about 7:3.

[0048] Desirably, the inorganic binder (A) is substantially optically transparent (e.g., the inorganic binder has a light transmittance of at least 80%, including from 90% up to 98%), as measured at a thickness of about 0.1 to about 0.2 millimeters using, for example, a spectrophotometer available from Idea Optics. In contrast, many inorganic binders are opaque.

[0049] In certain embodiments, the inorganic binders of the present disclosure can withstand high temperatures (e.g., above 200°C and up to 400°C, including 300°C or higher), have high light transmittance (e.g., at least 98%), have high tensile shear strength (e.g., at least 100 psi at 300°C), can be applied by a flexible coating process (e.g., dispensing, silk printing, spraying), and have low cure temperatures (e.g., below 185°C).

[0050] The reflective layer also contains reflective nanoparticles (B). The presence of the reflective nanoparticles is believed to reduce the shrinkage of the binder (A) and reduce the formation of cracks and bubbles. This avoids stress during assembly and improves the adhesion strength of the reflective layer to the substrate. Ideally, the thermal expansion coefficient of the reflective nanoparticles should be as close as possible to that of the binder (A), and their densities should also be as close as possible to avoid stratification of the components.

[0051] The reflective nanoparticles have a particle size of about 200 nanometers to about 500 nanometers, including about 300 nm to about 500 nm and about 350 nm to about 450 nm. The reflective nanoparticles can be made of pure titanium dioxide (TiO2) or modified TiO2. The modified TiO2 nanoparticles can be surface modified with organic alcohols, siloxanes, aluminum oxide (Al2O3), zirconium dioxide (ZrO2), or silicon dioxide (SiO2). In a preferred embodiment, the reflective nanoparticles are pure TiO2.

[0052] The weight ratio of the (B) reflective nanoparticles to the (A) binder may be from about 1:2.5 to about 1:0.8, including from about 1:2 to about 1:1. The reflective nanoparticles (B) need to be mixed with the binder (A), and then the mixture can be refrigerated before use. For example, the nanoparticles can be mixed with the binder twice, each time for about 2 minutes at 800 rpm, and then refrigerated at about 4° C. for about 24 hours. Desirably, the reflective nanoparticles are uniformly dispersed throughout the mixture, such that the reflective nanoparticles are also uniformly dispersed throughout the reflective layer.

[0053] The reflective layer can be formed by applying a mixture of binder (A) and reflective nanoparticles (B) to the substrate, which can be applied by dispensing, spraying, brushing, flowing, pattern coating or silk printing.

[0054] In applications where the mixture is applied by dispensing or silk printing, the mixture should have a suitable viscosity of about 0 to about 1,500 centipoise (cP), including about 100 to about 800 cP, or about 100 cP to about 600 cP, about 200 to about 500 cP, or about 1,000 cP to about 1,500 cP. The viscosity is measured using a Brookfield DVE SLVTJ0 viscometer or according to ASTM D1084. The inorganic binder itself (i.e., without TiO2 nanoparticles) may also have a suitable viscosity of about 0 to about 1,500 centipoise (cP), including about 0 to about 800 cP, or about 100 cP to about 800 cP.

[0055] In some examples, it is contemplated that the reflective layer is built up over multiple coating rounds. For example, in a first round, the mixture of binder (A) and reflective nanoparticles (B) is stirred and then sprayed onto the substrate to form a reflective layer having a thickness of about 0.025 mm to about 0.075 mm. This first layer is then left at room temperature for about 0.5 hours and then cured at about 85° C. for about 0.5 hours. In a second round, the mixture of binder (A) and reflective nanoparticles (B) is again stirred and then sprayed onto the first layer, left at room temperature for about 0.5 hours and then cured at about 85° C. for about 0.5 hours. This results in a final reflective layer having a total thickness of about 0.05 mm to about 0.15 mm.

[0056] The reflective layer is configured to reflect light over a wavelength range of desirably about 380 nm to about 800 nm, more preferably about 420 nm to about 680 nm. The reflectance of the reflective resin layer is typically at least 90% (or greater), more preferably at least 94% (or greater), or 95%, or 96%, or 97%, or 98%, or 99%.

[0057] The reflective layer may have a total thickness of about 0.05 mm to about 0.15 mm. In certain embodiments, the reflective layer has a thickness of about 0.7 mm to about 0.12 mm. The thickness will be set to maximize the reflectance of light output in the desired wavelength range. Thicker layers provide higher reflectance but may also cause long-term failure due to, for example, peeling or cracking of the reflective layer. Thus, the optimal thickness may be determined by some compromise between optimal reflectance and / or the reflectance and durability.

[0058] The reflective layer is generally different (and distinguishable) from the phosphor layer by its composition and / or structure. In particular, the reflective layer is generally significantly more reflective than the phosphor layer. The phosphor layer is generally not reflective. The reflective layer generally does not include a wavelength converting material (e.g., phosphor).

[0059] The reflective layers of the present disclosure containing reflective nanoparticles can maintain at least 95% total reflectance at temperatures above 200°C. They can be cured at relatively low temperatures between 85°C and 150°C. They exhibit reliable operation under high laser irradiance and temperature. They can also be flexibly fabricated in various sizes, shapes and thicknesses. They can also withstand high operating temperatures, i.e., above 200°C and up to 250°C. They can be used in high power laser projection display systems, where the solid state laser projector can have a laser power of about 60 watts to about 300 watts, including above 100 watts. The operating temperature of such devices can reach above 200°C to achieve high emission brightness.

[0060] In some embodiments, the reflective layer 120 can also function as an adhesive layer between the substrate 110 and the phosphor layer 130. Alternatively or additionally, a second adhesive layer (e.g., glue or tape) can be used to adhere the phosphor layer to the reflective layer. This can be useful for certain solid phosphor layers made from phosphor particles dispersed in glass, crystal, or ceramic materials, for example.

[0061] 1A and 1C, it should be noted that the width of the reflective layer 120 (measured radially on the substrate) can vary. In FIG. 1A, the width of the reflective layer 120 is much larger than the width of the phosphor layer 130. However, as illustrated in FIG. 1C, the width of the reflective layer 120 can also be approximately equal to the width of the phosphor layer 130. In general, the width of the reflective layer 120 can be at least equal to the width of the phosphor layer 130 and greater than the width of the phosphor layer.

[0062] It is believed that the reflective layers described herein can be used in phosphor wheels and laser projection display systems. They can also be used in conjunction with solid state lighting sources, for example in automobile headlights.

[0063] The following examples are provided to illustrate the processes of the present disclosure. The examples are merely illustrative and are not necessarily intended to limit the disclosure to the materials, conditions, or process parameters described therein. EXAMPLES

[0064] Example 1: Two phosphor wheels were fabricated with a reflective layer consisting of an inorganic binder and TiO2 nanoparticles. The inorganic binder of the reflective layer was formed from a first and a second component. The total dissolved solids (TDS) properties of the inorganic binders used are shown in the table below. [Table 2]

[0065] The mass ratio of inorganic binder to TiO2 nanoparticles was 1:1.7. The first wheel, labeled PT01, used TiO2 nanoparticles with particle size of 0.4-0.45 μm (i.e., 400-450 nm). The second wheel, labeled PT02, used TiO2 nanoparticles with particle size of 0.36 μm (i.e., 360 nm).

[0066] The inorganic binder and TiO2 nanoparticles were mixed in a mixer twice for 2 min each at 800 rpm to prepare the inorganic scattering layer material (ISLM).

[0067] Interestingly, ISLM acted as a shear-thinning fluid, i.e., its viscosity decreased when it was stirred. PT02 powder also clumps easily, causing the adhesive to not be fully absorbed. Therefore, the ISLM was placed in a refrigerator at 4°C for 24 hours to ensure that the inorganic binder was fully absorbed by the PT02 powder. After 24 hours, the ISLM was gently stirred by hand to ensure that the mixed material was homogenous. The viscosity of the ISLM was 1000-1500 centipoise (cP).

[0068] The ISLM was applied using an automatic sprayer (PVA350). The spray air pressure was adjusted to 3.5 MPa. The ISLM was sprayed twice onto the AI ​​disk to obtain a wet reflective layer. The wet layer was left at room temperature for 0.5 hour and cured at 85°F for 0.5 hour to obtain a reflective layer with a thickness of 0.045 mm. A second layer was applied on top of this first layer to obtain a reflective layer with a total thickness of 0.09 mm. The reflective layer was cured at 185°F for 0.5 hour to ensure that the layer was fully cured.

[0069] First, the diffuse reflectance of the PT01 and PT02 phosphor wheels was measured at various reflective layer thicknesses. The results for the PT01 phosphor wheel are shown in Figure 2A and Table A below. The results for the PT02 phosphor wheel are shown in Figure 2B and Table B below. As can be seen from these results, the reflectance stabilized above 94% for thicknesses above 0.08 mm (PT01) or 0.07 mm (PT02). [Table 3] [Table 4]

[0070] The two phosphor wheels PT01 and PT02 were then compared to two other phosphor wheels: the first comparative wheel, labeled G1, used only inorganic binders in the reflective layer (i.e., no TiO2 nanoparticles); the second comparative wheel, labeled G1.5, used only organic binders in the reflective layer (no TiO2 nanoparticles).

[0071] Output tests were performed at different thicknesses to compare the PT02 wheel with the G1 wheel. The results for the PT02 wheel are shown in Table C. In the last column, 100% is the result obtained with the G1 phosphor wheel. [Table 5]

[0072] Reliability tests were then performed comparing the PT02 and G1 wheels at 100W and 50W. The test conditions are shown in Table D. Three samples were run for each test. The results for the PT02 wheels are shown in Table E. Again, 100% is the result obtained with the G1 phosphor wheel. [Table 6] [Table 7]

[0073] Finally, the PT02 wheel was compared with the G1 wheel at 100W and 50W. The samples were placed in a muffle furnace at 250°C and the power performance was tested over time. The results for the PT02 wheel are shown in Table F. Again, 100% is the result obtained with the G1 phosphor wheel. The results showed that the PT02 wheel was stable and no cracks occurred between the reflective layer and the phosphor layer. [Table 8]

[0074] Output tests were performed at different thicknesses to compare the PT01 wheel with the G1 wheel. The results for the PT01 wheel are shown in Table G. In the last column, 100% is the result obtained with the G1 phosphor wheel. [Table 9]

[0075] Reliability tests were then performed comparing the PT01 and G1 wheels at 100W and 50W. The test conditions are shown in Table D above. Three samples were run for each test. The results for the PT01 wheels are shown in Table H. Again, 100% is the result obtained with the G1 phosphor wheel. [Table 10]

[0076] Finally, the PT01 wheel was compared with the G1 wheel at 100W and 50W. The samples were placed in a muffle furnace at 250°C and the power performance was tested over time. The results for the PT01 wheel are shown in Table I. Again, 100% is the result obtained with the G1 phosphor wheel. The results showed that the PT01 wheel was stable and no cracks occurred between the reflective layer and the phosphor layer. [Table 11]

[0077] Example 2: Diffusivity tests were performed with different types of nanoparticles of TiO2, Al2O3 and Al. The binder was an inorganic binder. Layers of different thicknesses were made and tested for diffusivity (i.e., diffuse reflectance). Table J shows five different mixtures and Table K provides the diffusivity results of three mixtures. Note that a given layer may have different thicknesses due to manual spraying of the mixtures. [Table 12] [Table 13]

[0078] The results in Table K show that the diffusivity of Al2O3 nanoparticles exceeds 94% when the layer thickness exceeds 0.15 mm. However, the reflectivity of Al2O3 is not stable (i.e., it varies widely) and requires a larger thickness than TiO2 nanoparticles to achieve the same reflectivity. Al2O3 is also prone to cracking. Therefore, it is concluded that TiO2 is the best nanoparticle to use in highly reflective layers.

[0079] Example 3: Diffusivity tests were performed with different TiO2 nanoparticles from different suppliers, as well as Al(OH)3 and MgO. The binder was an inorganic binder. Layers of different thickness were made and tested for diffusivity. Table L shows six different mixtures, and Table M provides the diffusivity results for five mixtures. Note that the MgO particles were large and could not be mixed uniformly. [Table 14] [Table 15]

[0080] Mixture #5 was able to obtain a diffusion coefficient of over 94%. The results also showed that the use of 0.2 μm and 0.5 μm TiO2 nanoparticles could obtain a diffusion coefficient of over 90%.

[0081] The present disclosure has been described with reference to preferred embodiments. Modifications and alterations will occur to others upon reading and understanding the preceding detailed description. It is intended that the present disclosure be construed as including all such modifications and alterations insofar as they come within the scope of the appended claims or the equivalents thereof.

Claims

1. A substrate; A reflective layer on the substrate, comprising: (A) a binder; and (B) a reflective titanium dioxide (TiO 2 ) nanoparticles, The binder (A) is an inorganic binder containing an inorganic sol-gel made of silicon dioxide or aluminum oxide, The (B) reflective titanium dioxide (TiO 2 The nanoparticles are made of organic alcohol, siloxane, and aluminum oxide (Al 2 O 3 ), zirconium dioxide (ZrO 2 ) or silicon dioxide (SiO 2 (B) is surface-modified with reflective titanium dioxide (TiO 2 a reflective layer in which the mass ratio of the nanoparticles to the binder (A) is 1:2 to 1:1; a wavelength converting layer on the reflective layer; and Equipped with A wavelength conversion device, wherein the reflective layer is thermally stable at an operating temperature of 250°C.

2. 2. The wavelength conversion device of claim 1, wherein the reflective layer has a thickness of 0.05 mm to 0.15 mm.

3. The (B) reflective titanium dioxide (TiO 2 2. The wavelength conversion device of claim 1, wherein the nanoparticles have a particle size of 350 nanometers to 450 nanometers.

4. 2. The wavelength conversion device of claim 1, wherein the reflective layer has a reflectance of at least 95% for light having a wavelength of 420 nm to 680 nm.

5. 2. The wavelength conversion device of claim 1, wherein the wavelength conversion layer is a phosphor layer comprising phosphor particles dispersed in a glass, crystal or ceramic material.

6. The wavelength conversion device according to claim 1 , wherein the substrate has a disk shape.

7. The wavelength conversion device of claim 1 , further comprising a motor for rotating the substrate.

8. The wavelength conversion device of claim 1 , wherein the substrate is a metal, a non-metallic material, or a composite material.

9. An optical projection system comprising the wavelength conversion device according to claim 1.

10. applying a composition to a substrate to form a reflective layer on the substrate, the composition comprising: (A) a binder; and (B) a reflective titanium dioxide (TiO 2 ) nanoparticles, The binder (A) is an inorganic binder containing an inorganic sol-gel made of silicon dioxide or aluminum oxide, The (B) reflective titanium dioxide (TiO 2 The nanoparticles are made of organic alcohol, siloxane, and aluminum oxide (Al 2 O 3 ), zirconium dioxide (ZrO 2 ) or silicon dioxide (SiO 2 (B) is surface-modified with reflective titanium dioxide (TiO 2 a weight ratio of the nanoparticles to the binder (A) is 1:2 to 1:1; curing the composition at a temperature between 85°C and 150°C; forming a wavelength converting layer on the reflective layer; Including, The method for manufacturing a wavelength conversion device, wherein the reflective layer is thermally stable at an operating temperature of 250°C.

11. The method of claim 10, wherein the composition has a viscosity of up to 1500 centipoise (cP).

12. The method of claim 10, wherein the composition is applied by dispensing, spraying, brushing, flowing, coating, or silk-screening.

13. Prior to application of the composition to the substrate, the composition is mixed with an organic alcohol, a siloxane, and aluminum oxide (Al 2 O 3 ), zirconium dioxide (ZrO 2 ) or silicon dioxide (SiO 2 ) and (B) reflective titanium dioxide (TiO 2 11. The method of claim 10, further comprising the step of: modifying the surface of the nanoparticles.

14. Prior to the step of applying the composition to a substrate and forming a reflective layer on the substrate, the (A) binder and the (B) reflective titanium dioxide (TiO 2 11. The method of claim 10, further comprising mixing the nanoparticles to form a mixture and refrigerating the mixture to form the composition.

Citation Information

Patent Citations

  • Light source device and projection-type display device including the light source device

    JP2013250481A

  • WAVELENGTH CONVERTER AND RELATED LIGHT EMITTING DEVICE

    JP2017517771A

  • Hybrid materials for use as means of coating optoelectronic components

    JP2017524158A

  • Fluorescent plate, light source device, and projection type video display device

    JP2019032506A

  • Improved wavelength conversion device

    JP2019501419A